The use of the bioinspired nodes with a variable center of rotation to optimize the moments in a portal frame - Kopytowska, Marta; Wirowski, Artur; Kozanecki, Damian; Bredow, Rafał (Archives of Civil Engineering, 2026)
This publication shows an algorithm for the design of a fully new ridge node in a steel, portal frame with a variable center of the rotation for the girders connected to it. The mechanics of the node was inspired by the mechanics of a bending movement of the human knee joint, due to a variable center of its rotation. This innovative structure of the ridge node can be optimized by any objective function that is based on the bending moments, occurring in the portal frame, for any chosen type of loads or their combinations. The proposed algorithm is presented using two specific examples of the portal frame for two, completely different objective functions. The results for both examples were compared to the benchmark model with a classic connection in the ridge, using an engineering program using finite elements analysis. The whole work was concluded by showing the results and potential directions for further development of such new technology.